Practice and school relationships: education imperatives. - Numerof RE (Nursing Management)
Succeeding in the year 2001 will require more than repackaging current curricula and adding a few more courses. It will call for a radical reexamination of nursing's role in the health delivery system--balancing detail and precision at the patient systems level with broad, analytic, integrative thinking.